Role of ChatGPT as an Innovative Tool for Data Analysis and Market Trend Prediction in Business Information Systems - Muhamad Malik Mutoffar; Sri Kuswayati; Tarsinah Sumarni; Rimba Krisnha Sukma Dewi; Erni Nurjanah (Politeknik Ganesha Medan, 2024)
The advancement of information and communication technology has fundamentally transformed the business landscape. Businesses are increasingly reliant on data to make effective, market-oriented decisions. Within the context of business information systems, ChatGPT can be utilized as an innovative tool to optimize data analysis processes, provide deeper market insights, and even make predictions about future trends. The aim of this research is to explore and test the potential of ChatGPT as an innovative tool in analyzing data and predicting market trends within the context of business information systems. This research employs a literature review approach with a qualitative methodology and descriptive analysis. Data were obtained from Google Scholar for the period of 2003-2024. The study results indicate that in an era where data has become the most valuable asset for companies, the ability to analyze and understand data effectively is key to success. In this context, the role of ChatGPT as an innovative tool for data analysis and market trend prediction in business information systems becomes highly significant. ChatGPT possesses the capability to comprehend and process human language with a high level of complexity, thus enabling it to harness data in various beneficial ways for companies.